"Western" Israel in the system of the oriental civilization = "Zachodni" Izrael w systemie orientalnej cywilizacji - Świeca, Jerzy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concentrates on defining of the civilization creature of the state Israel on the Middle East scene and on conditionings belongings of Israel both to the western system as and the eastern oriental world. The author gets to the bottom of the dynamics of the evolution of the demographic matter states as and into his scene of party-political which determines the external strategy and the policy.
Keywords: political system; constitutional conditionings; political arena; foreign strategy; demography; system polityczny; uwarunkowania konstytucyjne; arena polityczna; strategia zagraniczna; demografia